ASPEK MORAL DALAM NASKAH DRAMA 'LAKON JENG MENUL' KARYA PUTHUT BUCHORI - Candra Ayu Dyah Khoirun Nisa'; Hidayah Budi Qurani (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2021)
This study provides insight into the moral aspects of the characters in a drama script entitled Lakon Jeng Menul written by Puthut Buchori. Moral comes from habits or rules that a society has agreed to practice. The method used in conducting this research is qualitative methods with a descriptive type of research. The approach used in this study is a moral approach. The result of this study are various of moral aspects in the drama that can be divided into two opposite categories, namely: good and bad moralities. Among the fine morals reflected in the drama are: honesty, peacekeeping, autonomy, tolerance, cooperation, curiousity, law obedience, and politeness. Meanwhile, the bad moralities are shown by the acts of disrespecting spouse, dividing-and-conquering, thinking with prejudice, and being dishonest